2011
DOI: 10.1111/j.1532-5415.2011.03559.x
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Use of High‐Risk Medications for Older Veterans: 2004 to 2006

Abstract: OBJECTIVES To examine the change in use of “High Risk Medications for the Elderly,” as defined by the National Committee on Quality Assurance's Healthcare Effectiveness Data and Information Set (HEDIS) quality measure (HEDIS HRME), by older outpatient veterans over a three year time period. We also sought to identify risk factors for HEDIS HRME exposure overall, and among the most commonly used drug classes. DESIGN Longitudinal retrospective database analysis. SETTING Outpatient clinics within the Departme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 36 publications
3
33
0
Order By: Relevance
“…We did not have access to care received from Medicare which leads to incomplete ascertainment of emergency care or hospital admission, unlike VA mortality data which has been found to be very accurate. 21 Individuals with HRME or Rx-DIS tend to have more chronic disease 14, 15 and therefore may be more likely to receive hospital admission or emergency care in a Medicare setting than individuals without such exposure. Because that would bias toward the null hypothesis, we believe our results are conservative.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We did not have access to care received from Medicare which leads to incomplete ascertainment of emergency care or hospital admission, unlike VA mortality data which has been found to be very accurate. 21 Individuals with HRME or Rx-DIS tend to have more chronic disease 14, 15 and therefore may be more likely to receive hospital admission or emergency care in a Medicare setting than individuals without such exposure. Because that would bias toward the null hypothesis, we believe our results are conservative.…”
Section: Discussionmentioning
confidence: 99%
“…11, 25, 26 These variables were selected for inclusion in this analysis since they were identified as being associated with HRME and Rx-DIS in our prior research. 14, 15 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An analysis of data from all VA outpatient clinics focusing on individuals older than 65 years old found that increased number of medications was associated with exposure to any high-risk medication (OR = 1.13 [99 % CI 1.12, 1.13]). Increased number of medications was also associated with exposure to specific high-risk medications, including antihistamines (OR = 1.12 [99 % CI 1.11, 1.12]), opioids (OR = 1.10 [99 % CI 1.09, 1.10]), psychotropics (OR = 1.12 [99 % CI 1.12, 1.13]), and skeletal muscle relaxants (OR = 1.10 [99 % CI 1.10, 1.10]) [88]. These findings are consistent with other studies [89].…”
Section: Polypharmacy and Harmsmentioning
confidence: 99%
“…These databases are the repositories of clinical data from more than 150 VA hospitals and 850 outpatient clinics. Details regarding this study cohort have been previously published 25,26 .…”
Section: Methodsmentioning
confidence: 99%